Left ventricular diastolic dysfunction (LVDD) in Impaired Glucose Tolerance (IGT) patient - Bhuiyan, AKMM; Siddique, MA; Ahmed, MK; Ahmed, CM; Rahman, MM; Haque, KMHS S; Ahsan, SA; Karmakar, PK (University Heart Journal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The purpose of the study was to identify left ventricular diastolic dysfunction in patient with Impaired Glucose Tolerance. During the last few years it has been shown that IGT patient without IHD, Hypertension and other recognized cause of diastolic dysfunction also shown diastolic dysfunction. The study was carried out at the University Cardiac Center (UCC) Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during the period between July 2005 to Jun 2007. Insulin resistance is common. Therefore the present study was carried out of find out the frequency of LVDD in IGT subject and find out the association of LVDD in IGT with a view to detect diastolic dysfunction at early stage as we can take measure for prevention of its progression or to reverse the process. Â University Heart Journal Vol.4(1) January 2008